Modified Interpretations of the Supine Roll Test in Horizontal Canal BPPV Based on Simulations: How the Initial Position of the Debris in the Canal and the Sequence of Testing Affects the Direction of the Nystagmus and the Diagnosis - Bhandari, Anita; Bhandari, Rajneesh; Kingma, Herman; Strupp, Michael (Frontiers in Neurology, 2022)
Background and Objectives The aim of this study was to show with three-dimensional simulations how the diagnostic supine roll test (SRT) is affected by the initial position of the debris within the horizontal canal (hc) and study the nystagmus patterns on changing the sequence of testing and its impact on the diagnosis of the side of involvement in hc-BPPV. Methods A 3D dynamic simulation model was developed and applied based on reconstructed MRI images and fluid dynamics. Each semicircular canal was linked to the respective extraocular muscles to visualize nystagmus generated on stimulation of the canal. Results The simulations of hc-canalithiasis showed that the nystagmus pattern seen with the SRT are changed by the initial position of the otolith debris within the canal and the sequence of testing. The debris changes position during SRT so that sequential steps do not start at the initial position as previously assumed. The sequence of performing the SRT steps from the right or left side influences the nystagmus pattern generated: bilateral direction-changing, bilateral direction-fixed, and unilateral nystagmus can be seen in different test conditions. The SRT itself may even reposition the debris out of the canal. Conclusions and Clinical Implications Simulations provide a dynamic tool to study the diagnostic SRT in hc-canalithiasis. Starting the SRT from right or left has a major impact on the test outcome (unlike the Dix-Hallpike maneuver). The findings provide a new interpretation for the results of the SRT. The simulations explain the phenomenon of direction-fixed nystagmus as a logical consequence of starting the SRT with the head turned towards the non-affected side in hc-canalithiasis with debris in the ampullary arm. They also show that unilateral nystagmus seen on SRT indicates canalithiasis of the non-ampullary arm of the side opposite to the side of nystagmus. The generation of bilateral direction-changing, bilateral direction-fixed and unilateral nystagmus can be the cause of misdiagnoses, in terms of the affected side and underlying mechanisms. Finally, a recommendation for a standardized protocol for the sequence of positional tests should be established to ensure uniform interpretation of test results.